Climate-smart agriculture, agroecology and soil carbon: towards winning combinations - Saj, Stéphane; Torquebiau, Emmanuel (Perspective, 2018)
Version française de l'article Adaptation to climate change and its mitigation are some of the biggest challenges facing agriculture. In the global South, these challenges are associated with the need for food security. The arrival of climate change on the international agenda has prompted the recycling of a multitude of initiatives to address this problem, leading inevitably to the emergence of numerous controversies. However, although the scales and actors targeted may differ, all of these initiatives are trying in one way or another to provide technical, social, economic and political options to increase the climate resilience of agriculture. There is heated debate about three approaches, which focus on these relationships between agriculture and climate: climate-smart agriculture, agroecology and the 4 per 1000 Initiative on soil carbon. Beyond the conceptual differences and the sometimes partisan interpretations of these three approaches, agriculture in the Southern countries needs to take advantage of their potential synergies.